Implementation of psychiatric e-consultation in family medicine community health centers. (September 2019) - Lu, Jiayun; Ketterer, Emily; McGuire, Patricia
Psychiatric E-consult is an innovative model of psychiatric consultation via the electronic health record. The project was completed as a quality improvement effort within a residency program in order to increase timely access to psychiatric consultation. Over 100 electronic consultations were requested in the initial 20 months of this project. Questions ranged from assistance with medication management, diagnostic clarification, to referral to outside resources. Findings from this quality improvement project include that the e-consultation model enhanced primary care physicians' and associated primary care health professionals' management of behavioral issues, increased behavioral health knowledge, and subjectively improved patient care.